2014
DOI: 10.3109/15563650.2013.859263
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phosphatidylethanol blood concentrations for screening alcohol consumption in early pregnancy

Abstract: Our study presents a formal characterization of PEth blood concentrations for screening alcohol ingestion in first-trimester pregnant women. However, caution is recommended for overrepresenting either negative or positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Likelihood ratios suggested that the accuracy of PEth testing improved as PAE increased from low to moderate to heavy. However, findings of high levels of sensitivity (100%) and specificity (96%) in 1 study of heavy PAE 78 were not supported by 2 other studies in which sensitivity was 18% to 22%. 72,82 Hair Testing…”
Section: Blood Testingmentioning
confidence: 81%
See 4 more Smart Citations
“…Likelihood ratios suggested that the accuracy of PEth testing improved as PAE increased from low to moderate to heavy. However, findings of high levels of sensitivity (100%) and specificity (96%) in 1 study of heavy PAE 78 were not supported by 2 other studies in which sensitivity was 18% to 22%. 72,82 Hair Testing…”
Section: Blood Testingmentioning
confidence: 81%
“…Studies included data on participants from the United States (5), 72,74,79,81,82 Korea (2), 77,78 Spain (1), 83 South Africa (1), 73 and Finland (1), 80 and combined data from the United States and Jordan (1) 75 and Canada and Israel (1). 76 Diagnostic accuracy data were available for 8 types of biomarker: carbohydrate deficient transferrin (CDT), 72,80,82 ethyl sulfate (EtS), 72,82 ethyl glucuronide (EtG), 72,82,83 fatty acid ethyl esters (FAEEs), 72 -77, 79, 81 γ glutamyltransferase (GGT), 72,80,82 hemoglobin acetaldehyde adducts (Hb-Ach), 80 mean corpuscular volume (MCV), 80 and phosphatidylethanol (PEth) 72,78,82 within 6 matrices: meconium, 72 -77, 79 placenta, 81 maternal urine, 72,82 maternal blood, 72,78,80,82 maternal hair, 82,83 and infant blood.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations